Nurturing by nutrition: On the future of gut microbiota management strategies for autoimmune disease - Larsen, Olaf F. A. (Frontiers in Nutrition, 2023)
The incidence of autoimmune disease continues to rise, which urges for new prevention and treatment modalities. The composition of the gut microbiota is associated with both susceptibility and progression of disease. Nutrition significantly shapes the gut microbial composition, and poses as such a modality for both prevention and treatment / adjuvant therapy. At very young age, nutritional intervention targeting the gut microbiota is still possible within a one-size-fits all regime, accompanied by a relatively high effect size. As ageing results in higher interindividual variation induced by cumulative exposome factors, a more personalized approach is needed, having a higher effect size than that of current nutritional intervention. As such, supplementation of microbial consortia consisting of keystone taxa and microbial guilds that are involved in the pathophysiology seem a promising direction to lower the burden of autoimmune disease.